SOME ASPECTS OF THE REPRODUCTIVE BIOLOGY OF KRAI COB (Auxis thazard) IN SIBOLGA, NORTH SUMATERA - Gussasta Levi Arnenda; Fathur Rochman; Roy Kurniawan (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2022)
Tuna, tuna and skipjack (TTC) species in North Sumatra have contributed to world tuna production. One of the sources of neritic tuna caught in Indian Ocean waters (WPP 572 and 573) is tuna krai (Auxis thazard). Tongkol krai (Auxis thazard) has a high economic value in Indonesia, especially in the waters of Sibolga and its surroundings. Ensuring the sustainability of cob krai resources is an absolute must. The purpose of this study was to determine the reproductive biology of Tongkol Krai (Auxis thazard) in North Sumatra. Research on the Sibolga Archipelago Fisheries Port (PPN) in February, July, and October 2019. This study uses quantitative research using survey methods, with the sampling technique used in this study is purposive stratified sampling. The results showed that the correlation between length and weight of 118 Krai Cob W= 0.0078L 3.234, with a positive allometric growth pattern. Spread Length 25-41cmFL. Sex ratio 1:0.83 and not significantly different. The first time the gonads matured in females at 31.74cmFL, and 28.43cmFL in males. Female krai cob had TKG I 21.05%, TKG II 5.26%, TKG III 2.63%, TKG IV 63.17%, and TKG V 7.89%. Cob krai Male TKG I 8.69%, TKG II 4.34%, TKG III 8.69%, TKG IV 73.91%, and TKG 4.34%.